Benefit sharing model of hydropower development based on input perspective: a case study of Xiluodu project in China - Sun, Haibing; Li, Xuan; Duan, Yuefang; Zhang, Ningjing (Frontiers in Sustainable Food Systems, 2023)
Hydropower provides important support for achieving dual-carbon goal, but problems such as reservoir resettlement conflicts are common in developing countries, which have become a bottleneck of sustainable hydropower development. Fair distribution of benefits is the key to solve this dilemma. While the concept of benefit sharing as the fundamental guarantee for the sustainable livelihood of landless resettlers is gradually reaching consensus, the amount of benefit distribution has always been an outstanding issue. In order to quantify the amount of benefit sharing scientifically and reasonably, this paper constructs a benefit sharing model of hydropower development from the perspective of stakeholder input, and carries out a case analysis. The results indicate that the main stakeholders of hydropower projects include governments, development enterprises and reservoir resettlers. Their inputs are water or environmental resources, capital, and land resources, which produce hydropower resources. The net present value method can be used to construct the benefit sharing model. In this model, sharing amount of resettlers and other major stakeholders is the product of the sum of the present value of the net cash flow of hydropower projects and the proportion of their respective input. In view of many uncertainties, the grey prediction method and Monte Carlo simulation method are used to solve the model. The case of the Xiluodu hydropower station in China proves the rationality and operability of the model. The study also shows with reference to the model’s calculation results, a shared development fund can be established by drawing money from electricity generation income to ensure long-term benefits for resettlers, while considering the reasonable benefit of other stakeholders. The two are connected. It is expected to achieve a new pattern of mutual benefit and multi-win outcome, which are characterized by stable power station revenue, prosperity and stability of the reservoir area, and increased benefit and common wealth of resettlers. This paper may provide a convenient and novel analysis tool for benefit sharing systems.